Preparation method of nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper
Through the preparation method of nanocellulose/SiC/MXene-CoFeC composite electromagnetic shielding paper, the problems of poor electromagnetic shielding effect and poor toughness of wood fiber materials are solved, and efficient electromagnetic shielding performance and good mechanical properties are achieved, which are suitable for diversified market demand.
Patent Information
- Application Number
- CN202510048840.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-22
AI Technical Summary
The existing electromagnetic shielding materials of wood fibers have problems with poor electromagnetic shielding effect and poor toughness.
The preparation method of nanocellulose/SiC/MXene-CoFeC composite electromagnetic shielding paper is adopted, and the nanocellulose solution, MXene solution, CoFeC powder and positively charged SiC particles on the surface are mixed by mechanical stirring, and the composite electromagnetic shielding paper is prepared by vacuum suction filtration and natural air-drying treatment.
It significantly improves the toughness and electromagnetic shielding performance of the material, solves the weight, conductivity and mechanical properties of traditional materials, reduces production costs, has good biocompatibility, and is suitable for diversified market demand.
Smart Images

Figure CN119859940A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of flexible and ultra-thin electromagnetic shielding composite materials; specifically, it relates to a method for preparing nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper. Background Art
[0002] With the rapid development of the 5G era, new technologies are widely used, and the demand for electromagnetic shielding materials is increasing. There is an urgent need to develop a new type of flexible, ultra-thin, high-performance electromagnetic shielding material. In recent years, people have made many attempts in the research and development of electromagnetic shielding materials, but the existing materials still have obvious defects.
[0003] Some electromagnetic shielding materials based on metal materials are difficult to prepare into lightweight film-like materials due to the high density of the metal itself. In addition, the processing technology of metal materials is complicated and the cost is high, which is not conducive to large-scale production and wide application. Polymer-based electromagnetic shielding materials have also received some attention, but their conductivity is often unsatisfactory. Even if the conductivity is improved by adding conductive fillers, in actual operation, the uniformity of the dispersion of these fillers in the polymer matrix is difficult to ensure, resulting in unstable electromagnetic shielding performance and poor operability of the material. At the same time, the addition of a large amount of conductive fillers will also reduce the mechanical properties of the material and increase production costs. Some studies use wood fibers and other materials to prepare electromagnetic shielding materials, but due to the inherent characteristics of their structure and performance, shielding materials prepared from pure biomass materials have poor electromagnetic shielding effects, poor toughness and strength, and are difficult to meet the mechanical performance requirements in actual use. Summary of the invention
[0004] The purpose of the present invention is to solve the problems of poor electromagnetic shielding effect and poor toughness of existing wood fiber electromagnetic shielding materials, and to provide a method for preparing nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper.
[0005] A method for preparing a nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper is achieved by the following steps:
[0006] 1. Preparation of MXene solution:
[0007] Concentrated hydrochloric acid, LiF and Ti3AlC2 are mixed and reacted, and the solution after the reaction is centrifuged, washed, ultrasonicated and centrifuged in sequence, and the upper layer solution is taken to obtain a MXene solution;
[0008] 2. Preparation of CoFeC powder:
[0009] Cobalt nitrate hexahydrate and dimethylimidazole were used as raw materials to prepare Co-based ZiF-67 particles, and then the Co-based ZiF-67 particles were added to a ferric sulfate solution, mechanically stirred and then allowed to stand, then centrifuged and dried, and finally carbonized to obtain CoFeC powder.
[0010] 3. Surface treatment of SiC particles:
[0011] SiC nanoparticles were added to the PDDA solution, centrifuged and vacuum dried after magnetic stirring to obtain SiC particles with positive charges on the surface;
[0012] 4. Preparation of functional paper:
[0013] The above-mentioned MXene solution, nanocellulose solution, CoFeC powder and SiC particles with positive charge on the surface are mechanically stirred and mixed to obtain a mixed solution, and then 3 to 10 mL of the mixed solution is taken, vacuum filtered through a 0.15 nm pore size membrane with a diameter of 50 mm, and then naturally air-dried to obtain a nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper, thereby completing the preparation method.
[0014] Furthermore, the concentrated hydrochloric acid, LiF and Ti3AlC2 described in step 1 are mixed and reacted: specifically, 15-20 ml of 9 mol / L concentrated hydrochloric acid and 1-10 g of LiF are mixed and magnetically stirred for 5-30 min, and then 1-10 g of Ti3AlC2 is added and magnetic stirring is continued for 10-30 min, and then the etching reaction is stirred in an oil bath at 20-50°C for 12-24 h.
[0015] Further, the centrifugal washing, ultrasonication and centrifugation described in step 1, taking the upper solution: specifically, adding distilled water to the reacted solution for centrifugal washing until it is neutral, then taking the precipitate and adding 50-200 ml of distilled water, ultrasonicating at 20° C. for 12-24 hours, and finally centrifuging.
[0016] Further, the specific process of preparing Co-based ZiF-67 particles in step 2 is as follows:
[0017] a. Dissolve 0.5-2 g of cobalt nitrate hexahydrate in 1-100 ml of distilled water to obtain a cobalt nitrate hexahydrate solution; dissolve 1-5 g of dimethylimidazole in 1-100 ml of distilled water to obtain a dimethylimidazole solution;
[0018] b. Add the above dimethylimidazole solution dropwise into the cobalt nitrate hexahydrate solution, stir magnetically for 20 to 40 minutes, let stand for 12 to 24 hours, then centrifuge at 5000 to 10000 r / min for 3 to 10 minutes, take the purple precipitate and dry it at 60°C, and grind it to obtain Co-based ZiF-67 particles.
[0019] Furthermore, the mechanical stirring in step 2 is followed by standing, centrifugation and drying: specifically, mechanical stirring is performed for 10 to 30 minutes, followed by standing for 1 to 10 hours, followed by centrifugation at 5000 to 10000 r / min for 5 to 15 minutes, and then drying at 60°C.
[0020] Furthermore, the ferric sulfate solution in step 2 is prepared by dissolving 1 to 3 g of ferric sulfate in 1 to 100 ml of distilled water to obtain a ferric sulfate solution.
[0021] Furthermore, the carbonization treatment in step 2 is carried out by keeping the temperature at 400-1000° C. for 2-6 hours under the protection of an inert gas; the inert gas is nitrogen or argon.
[0022] Furthermore, in step 3, the amount of SiC nanoparticles used is 4 g, the concentration of the PDDA solution is 0.02-0.1 w%, and the amount used is 400 ml.
[0023] Furthermore, the magnetic stirring time in step 3 is 3 to 5 hours, the centrifugation condition is 5000 to 10000 r / min for 10 to 20 minutes, and the vacuum drying is vacuum drying at 60°C.
[0024] Furthermore, in step 4, the amount of the MXene solution is 1 to 30 ml, the concentration of the nanocellulose solution is 1 to 5 w%, the amount is 1 to 8 ml, the amount of the CoFeC powder is 0.01 to 0.2 g, and the amount of the SiC particles with positive charge on the surface is 0 to 0.05 g.
[0025] In the preparation of the nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper of the present invention, the introduced nanocellulose, by utilizing its renewable, low-cost and good biocompatibility characteristics, can significantly improve the toughness of the material with only a small amount of addition, so that it can form a membrane material with excellent performance. At the same time, the introduction of MXene materials with unique two-dimensional layered structure, ultra-light weight and excellent conductivity, synergistic effect with biomass materials, can not only effectively solve the weight and conductivity problems of the material, but also greatly improve the electromagnetic shielding performance, and through reasonable composite design, the mechanical properties of the material are guaranteed, the production cost is reduced, and good biocompatibility is possessed, overcoming many deficiencies of existing electromagnetic shielding materials, meeting diverse market demands, and having broad application prospects; realizing the development of electromagnetic shielding functional materials with light, thin and conformable characteristics, while promoting the widespread application of biomass materials, it promotes the application of electromagnetic shielding materials in weapon equipment defense systems and communication security fields.
[0026] The reaction principle of the present invention is: using flexible paper made of nanocellulose as the basic element, loading MOF-derived FeCo-C magnetic particles, SiC nanoparticles loaded with surface positive charges, and MXene layers to construct an ultra-thin paper-based composite material with a multi-component composite flexible structure. MXene materials have the characteristics of high conductivity and rich functional groups, which enable the MXene layer to be tightly bound to cellulose through hydrogen bonds, and the positive charges on the surface of SiC particles can form an electrostatic bond with MXene and nanocellulose. The introduction of magnetic materials and SiC particles and the construction of a multi-layer structure of two-dimensional MXene promote the "absorption-reflection-reabsorption" process of electromagnetic wave reflection, which can effectively enhance electromagnetic attenuation.
[0027] The beneficial effects of the present invention are as follows: the flexible paper made of nanocellulose is used as the base element to solve the problem of poor flexibility of traditional electromagnetic shielding materials; the MXene material dispersion has good liquid phase processing performance, which solves the problem of large thickness of traditional electromagnetic shielding materials; at the same time, because of its high conductivity and low infrared emissivity, the electromagnetic shielding performance is enhanced, further solving the problems of poor electromagnetic shielding effect and poor toughness of existing wood fiber electromagnetic shielding materials.
[0028] The present invention gives full play to the intrinsic properties of each component, enhances the interaction between each component and the interface to construct nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper, broadens the application scope of paper-based materials, and gives the materials new structures and new functions.
[0029] The present invention is suitable for the preparation of nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a SEM image of the nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper prepared in Example 1;
[0031] Figure 2 This is a graph of the electromagnetic shielding effectiveness of the nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper prepared in Example 1;
[0032] Figure 3 is a SEM image of the nanocellulose / MXene-CoFeC composite electromagnetic shielding paper prepared in Example 2;
[0033] Figure 4 This is a graph of the electromagnetic shielding effectiveness of the nanocellulose / MXene-CoFeC composite electromagnetic shielding paper prepared in Example 2;
[0034] Figure 5This is a physical picture of the flexible display of the nanocellulose / MXene-CoFeC composite electromagnetic shielding paper prepared in Example 2;
[0035] Figure 6 This is a SEM image of the nanocellulose / MXene composite electromagnetic shielding paper prepared in the comparative example;
[0036] Figure 7 This is a graph showing the electromagnetic shielding effectiveness of the nanocellulose / MXene composite electromagnetic shielding paper prepared in Comparative Example 1. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.
[0038] Specific implementation method 1: This implementation method is a method for preparing a nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper, which is achieved by the following steps:
[0039] 1. Preparation of MXene solution:
[0040] Concentrated hydrochloric acid, LiF and Ti3AlC2 are mixed and reacted, and the solution after the reaction is centrifuged, washed, ultrasonicated and centrifuged in sequence, and the upper layer solution is taken to obtain a MXene solution;
[0041] 2. Preparation of CoFeC powder:
[0042] Cobalt nitrate hexahydrate and dimethylimidazole were used as raw materials to prepare Co-based ZiF-67 particles, and then the Co-based ZiF-67 particles were added to a ferric sulfate solution, mechanically stirred and then allowed to stand, then centrifuged and dried, and finally carbonized to obtain CoFeC powder.
[0043] 3. Surface treatment of SiC particles:
[0044] SiC nanoparticles were added to the PDDA solution, centrifuged and vacuum dried after magnetic stirring to obtain SiC particles with positive charges on the surface;
[0045] 4. Preparation of functional paper:
[0046] The above-mentioned MXene solution, nanocellulose solution, CoFeC powder and SiC particles with positive charge on the surface are mechanically stirred and mixed to obtain a mixed solution, and then 3 to 10 mL of the mixed solution is taken, vacuum filtered through a 0.15 nm pore size membrane with a diameter of 50 mm, and then naturally air-dried to obtain a nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper, thereby completing the preparation method.
[0047] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the concentrated hydrochloric acid, LiF and Ti3AlC2 are mixed and reacted in step 1: specifically, 15-20 ml of 9 mol / L concentrated hydrochloric acid and 1-10 g of LiF are mixed and magnetically stirred for 5-30 min, and then 1-10 g of Ti3AlC2 is added and magnetically stirred for 10-30 min, and then the etching reaction is stirred in an oil bath at 20-50° C. for 12-24 h. The other steps and parameters are the same as those in specific embodiment 1.
[0048] Specific embodiment 3: This embodiment is different from specific embodiment 1 in that the centrifugal washing, ultrasonication and centrifugation described in step 1, taking the upper solution: specifically, adding distilled water to the solution after the reaction to perform centrifugal washing until it is neutral, then taking the precipitate and adding 50-200 ml of distilled water, ultrasonication at 20°C for 12-24 hours, and finally centrifugation. The other steps and parameters are the same as those of specific embodiment 1.
[0049] Specific embodiment 4: This embodiment is different from the specific embodiment 1 in that the specific process of preparing Co-based ZiF-67 particles in step 2 is as follows:
[0050] a. Dissolve 0.5-2 g of cobalt nitrate hexahydrate in 1-100 ml of distilled water to obtain a cobalt nitrate hexahydrate solution; dissolve 1-5 g of dimethylimidazole in 1-100 ml of distilled water to obtain a dimethylimidazole solution;
[0051] b. Add the above dimethylimidazole solution dropwise to the cobalt nitrate hexahydrate solution, stir magnetically for 20 to 40 minutes, let stand for 12 to 24 hours, then centrifuge at 5000 to 10000 r / min for 3 to 10 minutes, take the purple precipitate and dry it at 60° C., grind it to obtain Co-based ZiF-67 particles. Other steps and parameters are the same as those in the first embodiment.
[0052] Specific embodiment 5: This embodiment is different from specific embodiment 1 in that the mechanical stirring in step 2 is followed by standing, centrifugation and drying: specifically, mechanical stirring for 10 to 30 minutes, then standing for 1 to 10 hours, then centrifuging at 5000 to 10000 r / min for 5 to 15 minutes, and then drying at 60° C. The other steps and parameters are the same as those in specific embodiment 1.
[0053] Specific embodiment 6: This embodiment is different from specific embodiment 1 in that the ferric sulfate solution in step 2 is: 1-3 g of ferric sulfate is dissolved in 1-100 ml of distilled water to obtain a ferric sulfate solution. Other steps and parameters are the same as those in specific embodiment 1.
[0054] Specific embodiment 7: This embodiment differs from specific embodiment 1 in that the carbonization treatment in step 2 is carried out under the protection of an inert gas at 400-1000°C for 2-6 hours; the inert gas is nitrogen or argon. Other steps and parameters are the same as those in specific embodiment 1.
[0055] Specific embodiment 8: This embodiment differs from specific embodiment 1 in that the amount of SiC nanoparticles used in step 3 is 4 g, the concentration of PDDA solution is 0.02-0.1 w%, and the amount used is 400 ml. Other steps and parameters are the same as those in specific embodiment 1.
[0056] Specific embodiment 9: This embodiment is different from specific embodiment 1 in that the magnetic stirring time in step 3 is 3 to 5 hours, the centrifugation condition is 5000 to 10000 r / min for 10 to 20 minutes, and the vacuum drying is vacuum drying at 60° C. The other steps and parameters are the same as those in specific embodiment 1.
[0057] Specific embodiment ten: This embodiment is different from the specific embodiment one in that the amount of the MXene solution in step four is 1 to 30 ml, the concentration of the nanocellulose solution is 1 to 5 w%, the amount is 1 to 8 ml, the amount of the CoFeC powder is 0.01 to 0.2 g, and the amount of the SiC particles with positive surface charge is 0 to 0.05 g. The other steps and parameters are the same as those in the specific embodiment one.
[0058] The beneficial effects of the present invention are verified by the following examples:
[0059] Embodiment 1:
[0060] A method for preparing a nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper is achieved by the following steps:
[0061] 1. Preparation of MXene solution:
[0062] Concentrated hydrochloric acid, LiF and Ti3AlC2 are mixed and reacted, and the solution after the reaction is centrifuged, washed, ultrasonicated and centrifuged in sequence, and the upper layer solution is taken to obtain a MXene solution;
[0063] 2. Preparation of CoFeC powder:
[0064] Cobalt nitrate hexahydrate and dimethylimidazole were used as raw materials to prepare Co-based ZiF-67 particles, and then the Co-based ZiF-67 particles were added to a ferric sulfate solution, mechanically stirred and then allowed to stand, then centrifuged and dried, and finally carbonized to obtain CoFeC powder.
[0065] 3. Surface treatment of SiC particles:
[0066] SiC nanoparticles were added to the PDDA solution, centrifuged and vacuum dried after magnetic stirring to obtain SiC particles with positive charges on the surface;
[0067] 4. Preparation of functional paper:
[0068] The above-mentioned MXene solution, nanocellulose solution, CoFeC powder and SiC particles with positive charge on the surface are mechanically stirred and mixed to obtain a mixed solution, and then 10 mL of the mixed solution is taken and vacuum filtered through a 0.15 nm pore size membrane with a diameter of 50 mm, and then naturally air-dried to obtain nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper, thereby completing the preparation method.
[0069] In step 1 of this embodiment, the concentrated hydrochloric acid, LiF and Ti3AlC2 are mixed and reacted: specifically, 17 ml of 9 mol / L concentrated hydrochloric acid and 1 g of LiF are mixed and magnetically stirred for 30 min, then 1 g of Ti3AlC2 is added and magnetic stirring is continued for 30 min, and then the etching reaction is stirred in an oil bath at 40°C for 24 h.
[0070] In the step 1 of this embodiment, the centrifugal washing, ultrasonication and centrifugation are performed to take the upper solution: specifically, distilled water is added to the solution after the reaction and centrifuged until it is neutral, then the precipitate is taken and 700 ml of distilled water is added, ultrasonication is performed at 20° C. for 12 hours, and finally centrifugation is performed.
[0071] The specific process of preparing Co-based ZiF-67 particles in step 2 of this embodiment is as follows:
[0072] a. Dissolve 0.582 g of cobalt nitrate hexahydrate in 40 ml of distilled water to obtain a cobalt nitrate hexahydrate solution; dissolve 1.314 g of dimethylimidazole in 40 ml of distilled water to obtain a dimethylimidazole solution;
[0073] b. Add the above dimethylimidazole solution dropwise into the cobalt nitrate hexahydrate solution, stir magnetically for 30 min, let stand for 24 h, then centrifuge at 6000 r / min for 5 min, take the purple precipitate and dry it at 60°C, and grind it to obtain Co-based ZiF-67 particles.
[0074] In step 2 of this embodiment, the mechanical stirring is followed by standing, and then centrifugation and drying are performed: specifically, mechanical stirring is performed for 10 to 30 minutes, followed by standing for 1 to 10 hours, and then centrifugation is performed at 5000 to 10000 r / min for 5 to 15 minutes, and then drying is performed at 60°C.
[0075] The ferric sulfate solution in step 2 of this embodiment is as follows: 1.39 g of ferric sulfate is dissolved in 50 ml of distilled water to obtain a ferric sulfate solution.
[0076] In the carbonization treatment in step 2 of this embodiment, the temperature is kept at 600° C. for 5 hours under the protection of an inert gas; the inert gas is nitrogen.
[0077] In this embodiment, the amount of SiC nanoparticles used in step three is 4 g, the concentration of the PDDA solution is 0.1 w%, and the amount used is 400 ml.
[0078] In step 3 of this embodiment, the magnetic stirring time is 4 hours, the centrifugation condition is centrifugation at 8000 r / min for 15 minutes, and the vacuum drying is vacuum drying at 60°C.
[0079] In this embodiment, the amount of the MXene solution in step 4 is 1 to 30 ml, the concentration of the nanocellulose solution is 2.18 w%, the amount is 1 to 8 ml, the amount of CoFeC powder is 0.01 to 0.2 g, and the amount of SiC particles with positive charge on the surface is 0.05 g; and the total concentration of MXene, nanocellulose, CoFeC and SiC particles with positive charge on the surface in the mixed solution of step 4 is ensured to be 5 mg / ml.
[0080] In this embodiment, the 0.15 nm pore size membrane with a diameter of 50 mm was purchased from Shanghai Xinya Purification Device Field Microporous Filter Membrane.
[0081] The nanocellulose in this example was purchased from Tianjin Wood Elf Biotechnology Co., Ltd. and was TEMPO cellulose nanofiber.
[0082] The nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper prepared in this embodiment has a specific microscopic morphology SEM image as shown in Figure 1 As shown. MXene has a distinct layered structure, and there is a good interface bonding between the MXene layer and the nanocellulose. Compared with the comparative example, due to the addition of CoFeC powder, the CoFe particles are evenly distributed in MXene and nanocellulose. In addition, the added SiC particles improve the impedance matching of the paper-based functional material, which helps to attenuate the electromagnetic wave.
[0083] The electromagnetic shielding effectiveness of the nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper prepared in this embodiment is as follows: Figure 2 As shown, the electromagnetic shielding effectiveness SE greater than 35dB can be achieved in the X-band T , indicating that the functional paper prepared in this embodiment has excellent electromagnetic shielding performance.
[0084] Embodiment 2:
[0085] The difference between this embodiment and embodiment 1 is that the amount of SiC particles with positive surface charge in step 4 is 0; the rest is the same as embodiment 1.
[0086] The nanocellulose / MXene-CoFeC composite electromagnetic shielding paper prepared in this example has a specific microscopic morphology SEM image as shown in the following figure. Figure 3 As shown in the figure, MXene has a distinct layered structure, and there is a good interface bonding between the MXene layer and the nanocellulose. Compared with the comparative example, due to the addition of CoFeC powder, the CoFe particles are evenly distributed in MXene and nanocellulose.
[0087] The electromagnetic shielding effectiveness of the nanocellulose / MXene-CoFeC composite electromagnetic shielding paper prepared in this embodiment is as follows: Figure 4 As shown, an electromagnetic shielding effectiveness SE of nearly 28.5dB can be achieved in the X-band T , indicating that the functional paper prepared in this embodiment has excellent electromagnetic shielding performance.
[0088] The nanocellulose / MXene-CoFeC composite electromagnetic shielding paper prepared in this embodiment is flexible, and the actual picture showing its flexibility is as follows: Figure 5 shown.
[0089] Comparative Example:
[0090] The difference between the comparative example and the embodiment 1 is that in step 4, the amount of SiC particles with positive charges on the surface is 0, and the amount of CoFeC powder is 0; the rest is the same as the embodiment 1.
[0091] In the comparative example, nanocellulose / MXene composite electromagnetic shielding paper was prepared.
[0092] The nanocellulose / MXene composite electromagnetic shielding paper was prepared in the comparative example; the specific microscopic morphology SEM image is shown as follows Figure 6 As shown, it can be seen that MXene has an obvious layered structure, and there is a good interface bonding between the MXene layer and nanocellulose.
[0093] The nanocellulose / MXene composite electromagnetic shielding paper was prepared in the comparative example, and its electromagnetic shielding efficiency is as follows: Figure 7 As shown, an electromagnetic shielding effectiveness SE of nearly 16.5dB can be achieved in the X-band T .
[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper, characterized in that It proceeds as follows:
1. Preparation of MXene solution: Concentrated hydrochloric acid, LiF and Ti3AlC2 are mixed and reacted, and the solution after the reaction is centrifuged, washed, ultrasonicated and centrifuged in sequence, and the upper layer solution is taken to obtain a MXene solution; 2. Preparation of CoFeC powder: Cobalt nitrate hexahydrate and dimethylimidazole were used as raw materials to prepare Co-based ZiF-67 particles, and then the Co-based ZiF-67 particles were added to a ferric sulfate solution, mechanically stirred and then allowed to stand, then centrifuged and dried, and finally carbonized to obtain CoFeC powder.
3. Surface treatment of SiC particles: SiC nanoparticles were added to the PDDA solution, centrifuged and vacuum dried after magnetic stirring to obtain SiC particles with positive charges on the surface; 4. Preparation of functional paper: The above-mentioned MXene solution, nanocellulose solution, CoFeC powder and SiC particles with positive charge on the surface are mechanically stirred and mixed to obtain a mixed solution, and then 3 to 10 mL of the mixed solution is taken, vacuum filtered through a 0.15 nm pore size membrane with a diameter of 50 mm, and then naturally air-dried to obtain a nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper, thereby completing the preparation method.
2. The method for preparing a nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper according to claim 1, characterized in that The concentrated hydrochloric acid, LiF and Ti3AlC2 described in step 1 are mixed and reacted: specifically, 15-20 ml of 9 mol / L concentrated hydrochloric acid and 1-10 g of LiF are mixed and magnetically stirred for 5-30 min, and then 1-10 g of Ti3AlC2 is added and magnetic stirring is continued for 10-30 min, and then the etching reaction is stirred in an oil bath at 20-50°C for 12-24 h.
3. The method for preparing a nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper according to claim 1, characterized in that The centrifugal washing, ultrasonication and centrifugation described in step 1, and taking the upper solution: specifically, adding distilled water to the reacted solution for centrifugal washing until it is neutral, then taking the precipitate and adding 50-200 ml of distilled water, ultrasonicating at 20°C for 12-24 hours, and finally centrifuging.
4. The method for preparing a nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper according to claim 1, characterized in that The specific process of preparing Co-based ZiF-67 particles described in step 2 is as follows: a. Dissolve 0.5-2 g of cobalt nitrate hexahydrate in 1-100 ml of distilled water to obtain a cobalt nitrate hexahydrate solution; dissolve 1-5 g of dimethylimidazole in 1-100 ml of distilled water to obtain a dimethylimidazole solution; b. Add the above dimethylimidazole solution dropwise into the cobalt nitrate hexahydrate solution, stir magnetically for 20 to 40 minutes, let stand for 12 to 24 hours, then centrifuge at 5000 to 10000 r / min for 3 to 10 minutes, take the purple precipitate and dry it at 60°C, and grind it to obtain Co-based ZiF-67 particles.
5. The method for preparing a nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper according to claim 1, characterized in that The mechanical stirring in step 2 is followed by standing, centrifuging and drying: specifically, mechanical stirring for 10 to 30 minutes, then standing for 1 to 10 hours, then centrifuging at 5000 to 10000 r / min for 5 to 15 minutes, and then drying at 60°C.
6. The method for preparing a nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper according to claim 1, characterized in that The ferric sulfate solution in step 2 is prepared by dissolving 1 to 3 g of ferric sulfate in 1 to 100 ml of distilled water to obtain a ferric sulfate solution.
7. The method for preparing a nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper according to claim 1, characterized in that The carbonization treatment in step 2 is carried out by keeping the temperature at 400-1000° C. for 2-6 hours under the protection of an inert gas; the inert gas is nitrogen or argon.
8. The method for preparing a nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper according to claim 1, characterized in that The amount of SiC nanoparticles used in step 3 is 4 g, the concentration of PDDA solution is 0.02-0.1 w%, and the amount used is 400 ml.
9. The method for preparing a nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper according to claim 1, characterized in that The magnetic stirring time in step 3 is 3 to 5 hours, the centrifugal condition is centrifugation at 5000 to 10000 r / min for 10 to 20 minutes, and the vacuum drying is vacuum drying at 60°C.
10. The method for preparing a nanocellulose / SiC / MXene-CoFeC composite electromagnetic shielding paper according to claim 1, characterized in that In step 4, the amount of the MXene solution is 1 to 30 ml, the concentration of the nanocellulose solution is 1 to 5 w%, the amount is 1 to 8 ml, the amount of the CoFeC powder is 0.01 to 0.2 g, and the amount of the SiC particles with positive charge on the surface is 0 to 0.05 g.
Citation Information
Cited By
Low-reflection type electromagnetic shielding composite paper and preparation method thereof
CN120625427A